THE RISE OF THE PROFIT DEFERRAL NOTION: The Concept and Practice of Optimeasurement. - Jacobsen, Lyle E. (The Accounting Review, 1963)
Accountants appear to have backed off a bit from the "forgetting of income" movement of the "dirty surplus era" and to be content merely with deferring the recognition of income. Postponement of the recognizing of income or profit is attainable by means of several techniques, which have been developed over the years and which have gained varying degrees of prominence in the literature of accounting. In this paper, the author proposes to examine some of these techniques and to explain a relationship among them. This examination requires the clarification of a few terms. Some accountants have described aptly the term-deferred income as a misnomer. Profit deferral or income deferral, however, are understood to mean the process of postponing or deferring the recognition in the accounts of some arithmetic difference between revenues and expenses. Thus, deferral of income does not mean a delay in the obtaining or acquiring of income such as is the case when an individual is unemployed or a business makes no sales. To some accountants, the concept of optimeasurement which results in income deferral and presumably tax avoidance currently conflicts with a possible desire of management to show in some periods higher profits than optimeasurement would provide.